Kesantunan Pragmatik Buya Hamka dalam Refleksi Novel Ayah Karya Irfan Hamka - Riris Tiani (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2017)
Every one know Islamy person Buya Hamka. Buya said that politeness speech using not only to older people, but must begin from older people to younger’s one. Politeness speech also reflected leveling believed in God. The purpose of this study is to describe the form of courtesy speech Buya Hamka reflected in Irfan Hamka's novel AYAH. This research approach uses qualitative approach in Pragmatic study especially focuss on Politeness Pragmatics. Methods of data provision using the method refer to the technique of note, while the method of analysis using the contextual method with the theory Politeness Principle of Geoffrey Leech. The results of this study include a form of politeness consisting of two tact maxims, three generosity maxims, five sympathy maxims. Politeness principles has been formed on phares and sentences. Another result is nonlanguage factors which influence on Novel AYAH by Irfan Hamka using proverb in their speech.